2000
DOI: 10.1177/089198870001300101
|View full text |Cite
|
Sign up to set email alerts
|

Electroencephalographic Coherence in Alzheimer's Disease: Comparisons with a Control Group and Population Norms

Abstract: Previous research from independent laboratories has shown reduced electroencephalographic coherence in patients diagnosed with dementia of the Alzheimer type (DAT). This study added to this work by comparing interhemispheric and intrahemispheric coherence in nonmedicated DAT patients (n = 35) with that of a normal control group (n = 30), as well as with a data bank of population norms. Raw and Z-score transformed values showed reduced coherence, interhemispherically (in delta, theta, alpha, and beta bands) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
84
0
5

Year Published

2000
2000
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(105 citation statements)
references
References 39 publications
(10 reference statements)
14
84
0
5
Order By: Relevance
“…A decrease of resting state functional connectivity in Alzheimer's disease patients in the alpha and often also in the beta band has been reported in many EEG and MEG studies (Leuchter et al, 1992;Besthorn et al, 1994;Dunkin et al, 1994;Jelic et al, 1996;Locatelli et al, 1998;Knott et al, 2000;Stevens et al, 2001;Adler et al, 2003;Hogan et al, 2003;Jiang 2005;Koenig et al, 2005;Pogarell et al, 2005). However, a major point of criticism is that such studies were done on the raw EEG and MEG time series.…”
Section: Volume Conductionmentioning
confidence: 97%
See 1 more Smart Citation
“…A decrease of resting state functional connectivity in Alzheimer's disease patients in the alpha and often also in the beta band has been reported in many EEG and MEG studies (Leuchter et al, 1992;Besthorn et al, 1994;Dunkin et al, 1994;Jelic et al, 1996;Locatelli et al, 1998;Knott et al, 2000;Stevens et al, 2001;Adler et al, 2003;Hogan et al, 2003;Jiang 2005;Koenig et al, 2005;Pogarell et al, 2005). However, a major point of criticism is that such studies were done on the raw EEG and MEG time series.…”
Section: Volume Conductionmentioning
confidence: 97%
“…It has even been suggested that Alzheimer's disease can be viewed as a disconnection syndrome (Delbeuck et al, 2003). Support for this concept comes from a number of EEG and magneto-encephalography (MEG) studies using conventional coherence as a measure of functional connectivity (Leuchter et al, 1992;Besthorn et al, 1994;Dunkin et al, 1994;Jelic et al, 1996;Locatelli et al, 1998;Berendse et al, 2000;Knott et al, 2000;Stevens et al, 2001;Adler et al, 2003;Hogan et al, 2003;Jiang 2005;Koenig et al, 2005;Pogarell et al, 2005). In most of these studies a consistent decrease of coherence in the alpha and beta band was reported, whereas results for other bands were more variable.…”
Section: Introductionmentioning
confidence: 93%
“…They also found that 22% of normal controls had a BIS XP < 93; demonstrating wide interindividual variability and limiting its potential diagnostic use clinically. The quantitative EEG has been used as a research tool in the diagnosis of dementia; however, it has yet to demonstrate proven diagnostic utility [15].…”
Section: Discussionmentioning
confidence: 99%
“…In comparison with normal controls, there is increased activity in the theta band in subjects with Alzheimer's disease (AD), which is accompanied by an increase in delta activity and decreases in the alpha and beta bands 4 . In studies on coherence in AD, the most consistent finding has been a reduction in coherence in the alpha band [5][6][7] . There is still insufficient scientific evidence of the diagnostic utility of qEEG to establish this method for the initial evaluation of subjects with cognitive impairment in routine clinical practice 8 .…”
mentioning
confidence: 97%